IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT PADA APLIKASI E-COMMERCE UNTUK MEMBANTU MENYELEKSI BUSANA MUSLIM SESUAI KARAKTERISTIK KONSUMEN - Tanjung, Yuliani; Bulan, Semlinda Juszandri (JITU, 2018)
Daya Abadi Shop is a place that provides various products muslim fashion to Muslim women. The sales strategy which is in use now still wearing convensional system. The first is marketing still no media promotion. The problem, the clerk having difficulties to explain the appropriate fashion characteristics, and third from aspect of where the sales transaction data and customer data is still the recording manually. The purpose of this research is to implement E-Commerce and Customer Relationship Management in selling of muslim fashion on Daya Abadi Fashion Shop. The research methodology used was qualitative research. Website Development method E-Commerce based on Customer Relationship Management made adjust with research procedures. The approach method with structured and analysis tools in the form of system design document flow, context diagram, data flow diagram and design of the proposed database form entity relationship diagram. While the creation of the software in this thesis, the writer uses PHP and Adobe Dreamwaver CS3 and MySQL databases. The research results show that the E-Commerce based on Customer Relationship Management can help the Daya Abadi Shop in the selling of muslim fashion.